2011
DOI: 10.4322/floram.2011.064
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da umidade da madeira Pinus caribaea na propagação de ondas mecânicas da tomografia de impulso

Abstract: RESUMOA análise tomográfica de impulso é um método não destrutivo que permite analisar o interior do lenho de árvores pela passagem de ondas produzidas mecanicamente, tornando possível realizar uma avaliação prévia e detectar a presença de defeitos na madeira. Neste estudo, utilizouse o tomógrafo de impulso ARBOTOM para analisar o lenho de árvores de Pinus caribaea e associar o efeito da umidade na formação da imagem tomográfica. Os resultados mostraram que existe uma associação entre a umidade da madeira e a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…This effect could also be explained by the variation of the moisture content (MC%) of the wood at the time of the tomography (Bucur, 2005). Latorraca et al (2011) checking the relationship between moisture content (MC%) of wood and MPS from Pinus caribaea, concluded that moisture influences the formation of the tomographic image and that higher MC% results in lower MPS. Longitudinally, the authors observed that the humidity in the higher zone discs was higher than in the lower zone discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect could also be explained by the variation of the moisture content (MC%) of the wood at the time of the tomography (Bucur, 2005). Latorraca et al (2011) checking the relationship between moisture content (MC%) of wood and MPS from Pinus caribaea, concluded that moisture influences the formation of the tomographic image and that higher MC% results in lower MPS. Longitudinally, the authors observed that the humidity in the higher zone discs was higher than in the lower zone discs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies validated the use of tomography to determine the physical properties of wood, such as resistographic amplitude (Rollo et al, 2013), moisture content (Putri et al, 2017); Latorraca et al, 2011), and mechanical properties (Young and shear modulus) (Gonçalves et al, 2014;Gonçalves et al, 2011;Sedik et al, 2010), elasticity modulus (Carrasco et al, 2017), knots interference, juvenile wood, and reaction wood (Palma et al, 2018). Also, research was carried out to determine the pith´s location (Perlin et al, 2018) and address aspects related to wood anisotropy (Perlin et al, 2019;Arciniegas et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…As propriedades físicas da madeira de várias espécies variam conforme o raio de crescimento. A porção da madeira correspondente aos primeiros anéis de crescimento formados apresenta menor massa específica e fibras mais curtas, entre outras características, o que mostra as diferenças entre um lenho juvenil e um lenho adulto (Latorraca & Albuquerque, 2000).…”
Section: Densidade Básicaunclassified
“…A variação da densidade no sentido medula-casca é dependente da espécie em estudo; não há uma regra de disposição da mesma, porém, para a maioria das espécies de Eucalyptus, há tendência de aumento da densidade nesse sentido (Latorraca & Albuquerque, 2000). A Figura 2 mostra a tendência de variação encontrada por Carneiro (2017), para clones de Eucalyptus grandis x Eucalyptus urophylla, aos 6 anos de idade.…”
Section: Densidade Básicaunclassified
“…A tomografia baseada na velocidade de propagação da onda ultrassônica vem sendo utilizada na detecção de não homogeneidades em seções transversais de elementos de madeira (PRIETO e LASAY-GUES, 2014). Muitos são os trabalhos desenvolvidos com o emprego de softwares comerciais como: AR-BOTOM® (AMODEI et al, 2010;LATORRACA et al, 2011), FAKOPP® (CANDIAN e SALES, 2009;PADUEL-LI, 2011), MIGRATON® (MARTINIS et al, 2004;SAM-BUELLI et al, 2003) e PICUS® (DEFLORIO et al, 2007;WANG et al, 2009).…”
Section: Introductionunclassified